Cell type-specific localization of Ephs pairing with ephrin-B2 in the rat postnatal pituitary gland - Yoshida, Saishu; Kato, Takako; Kanno, Naoko; Nishimura, Naoto; Nishihara, Hiroto; Horiguchi, Kotaro; Kato, Yukio (Cell and tissue research, 2017)
Sox2 -expressing stem/progenitor cells in the anterior lobe of the pituitary gland form two types of micro-environments (niches): the marginal cell layer and dense cell clusters in the parenchyma. In relation to the mechanism of regulation of niches, juxtacrine signaling via ephrin and its receptor Eph is known to play important roles in various niches. The ephrin and Eph families are divided into two subclasses to create ephrin/Eph signaling in co-operation with confined partners. Recently, we reported that ephrin-B2 localizes specifically to both pituitary niches. However, the Ephs interacting with ephrin-B2 in these pituitary niches have not yet been identified. Therefore, the present study aims to identify the Ephs interacting with ephrin-B2 and the cells that produce them in the rat pituitary gland. In situ hybridization and immunohistochemistry demonstrated cell type-specific localization of candidate interacting partners for ephrin-B2, including EphA4 in cells located in the posterior lobe, EphB1 in gonadotropes, EphB2 in corticotropes, EphB3 in stem/progenitor cells and EphB4 in endothelial cells in the adult pituitary gland. In particular, double-immunohistochemistry showed cis -interactions between EphB3 and ephrin-B2 in the apical cell membranes of stem/progenitor cell niches throughout life and trans -interactions between EphB2 produced by corticotropes and ephrin-B2 located in the basolateral cell membranes of stem/progenitor cells in the early postnatal pituitary gland. These data indicate that ephrin-B2 plays a role in pituitary stem/progenitor cell niches by selective interaction with EphB3 in cis and EphB2 in trans .